The Turkish Economy After The Crisis - Dani Rodrik (Turkish Economic Association, 2009)
The recent crisis has demonstrated that a financially open economy has many sources of vulnerability. Even when a country does its homework, it remains at the mercy of developments in external financial markets. So, one lesson is that policy needs to guard not just against domestic shocks, but also shocks that emanate from financial instability elsewhere. Complete financial openness is not the best policy. A second lesson is that Turkeys prevailing growth strategy does not generate enough growth and employment. Therefore it would be a mistake for the country to return to the status quo ante and resuscitate a model that fails to make adequate use of domestic resources. Most importantly, Turkey has to learn to live with reduced reliance on external borrowing. The paper discusses the needed realignments in fiscal and exchange-rate policies.
Keywords: 330; Wirtschaftskrise; Wirtschaftswachstum; Türkei